Common snook juveniles, Centropomus undecimalis, as biomonitor organisms to evaluate cytogenotoxicity effects of surface estuarine water from Southern Brazil - Cardoso, Caroline Margonato; Maluf, Auro; Moreno, Beatriz Barbosa; Nobre, Caio Rodrigues [UNESP]; Maranho, Luciane Alves [UNESP]; Handan, Bianca Andrade; Abessa, Denis Moledo de Souza [UNESP]; Pereira, Camilo Dias Seabra; Ribeiro, Daniel Araki (Elsevier, 2019)
Centropomus undecimalis fish inhabit the highly contaminated Santos-São Vicente Estuarine System (SESS) and could be a good biomonitor of contaminants. This study aimed to investigate the cytogenotoxic potential of superficial water from SESS using C. undecimalis as a biomonitoring model and to validate the use of farmed fish as controls. Using biochemical (DNA damage and Lipid Peroxidation - LPO), cellular (erythrocyte nuclear abnormality – ENA) and tissue (8-OHdG immunoexpression) biomarkers, our results showed fish from SEES had higher LPO concentration in gills and higher frequency of reniform, lobed and total ENA in erythrocytes when compared with control farmed fish. Thus, SESS surface water are cytogenotoxic for blood and gills cells of fishes. C. undecimalis has shown to be a good biomonitor model and farmed fish can be used as control only if livers were not the target organs of study since the dietary food from farmed fish causes steatosis.
Keywords: 8-OHdG immunoexpression; DNA damage; Erythrocyte nuclear abnormality; Lipid peroxidation; Santos-São Vicente Estuarine System